Groundwater pollution impact on the rural areas - Baliga Daiana L.; Octavian Stana (2012)
This paper presents the impact of groundwater pollution on the land around irregular deposits on bordering rural communities. Rural area has the ability to preserve and restore the natural environment due to reduced anthropogenic pressure, associated with the type of economic exploitation and general development level of productive forces. Environmental quality of rural life has important antistress effects and therefore it is considered a heritage of humanity and should be kept. The paper is particularly important because we have taken into account that aquifer is an important source of water. Pollution is a serious problem affecting the environment and human health, in this case we want to present the study on pollution spreading. Historical pollution site has not been seen to be dangerous, till now. The purpose of this paper is to highlight the influence of pollution on rural areas in the neighborhood of inappropriate landfills and dumps storing waste or byproducts from various industries. In this paper we show the evolution of the pollutant plume from the landfill Şag-Parţa and a slag and ash dump Utvin, Timiş county. Both deposits are located near the town of Timişoara. The models presented in this paper were performed using MODFLOW software.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok; Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat